Becoming an Impactor: How Do Leaders Empower the Poor: The Role of Inclusive Leadership in Capability Development - Fujimoto, Yuka *; Uddin, Jasim (2020)
Prior research has examined several approaches to inclusive leadership and the inclusion of skilled employees but has neglected to focus on unskilled, low-income individuals. By studying leaders who employ the poor and marginalized in their social enterprises, we develop a new theoretical framework for understanding how leaders may effectively include the poor in their businesses. Based on Amartya Sen’s capability approach, we contribute a granular understanding of how leaders foster economic inclusion of the poor. Extending beyond the current development of inclusive leadership theory for work group effectiveness, we provide a fresh perspective of inclusive leadership for the poor and marginalized.